Proceedings of the 6th International Conference on Mobile Technology, Application &Amp; Systems - Mobility '09 2009
DOI: 10.1145/1710035.1710096
|View full text |Cite
|
Sign up to set email alerts
|

A pervasive gesture-driven augmented reality prototype using wireless sensor body area networks

Abstract: This paper describes the prototype implementation of a pervasive, wearable augmented reality (AR) system based on a full bodymotion-capture system using low-power wireless sensors. The system uses body motion to visualize and interact with virtual objects populating AR settings. Body motion is used to implement a whole body gesture-driven interface to manipulate the virtual objects. Gestures are mapped to correspondent behaviors for virtual objects, such as controlling the playback and volume of virtual audio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Data provided by these sensors are analyzed to assess, for instance, the physical ability of users, determining if a movement is properly executed, to know the speed reached, the amount of calories and fat burned, your heart rate, or the distance traveled in the exercise [4]. Moreover, BANs are also utilized in virtual and augmented reality to detect body movements or hand gestures to interact with objects within a virtual environment [38]. Another approach presents a wearable composed of three-axis absolute orientation sensor, accelerometer and gyroscope [39].…”
Section: Wearable Sensors In Healthcarementioning
confidence: 99%
“…Data provided by these sensors are analyzed to assess, for instance, the physical ability of users, determining if a movement is properly executed, to know the speed reached, the amount of calories and fat burned, your heart rate, or the distance traveled in the exercise [4]. Moreover, BANs are also utilized in virtual and augmented reality to detect body movements or hand gestures to interact with objects within a virtual environment [38]. Another approach presents a wearable composed of three-axis absolute orientation sensor, accelerometer and gyroscope [39].…”
Section: Wearable Sensors In Healthcarementioning
confidence: 99%
“…Restrictive interaction has been shown to be detrimental to task performance, Barrie et al [4] attempted to design a system in which virtual objects can be manipulated in an augmented reality but results showed that the use of low powered wireless sensors (Figure 2.14) and headset became cumbersome and impractical. The system was restricted by the headset connections and also assumes that the user is fixed is space, meaning only the top half of the body is used to capture.…”
Section: Hand and Body Gesturesmentioning
confidence: 99%
“…Augmented and mixed reality are concepts that have been used around technology for a few years [3] [5]. However, their coupling with mobile devices has only been made possible more recently with the advent of powerful smart-phones.…”
Section: Motivation and Related Workmentioning
confidence: 99%
“…Moreover, as previous work has shown, augmented reality provides new affordances and visualization options that enhance experiences by providing additional information combined with the real world surroundings of the users [2][3][5] [8]. By placing virtual objects or feedback over reality users are provided access to information that is typically not available to them using their own senses [3]. Naturally, this gains further relevance with mobile technology as users move around and are able to explore what is around them freely within real world settings [1] [5].…”
Section: Motivation and Related Workmentioning
confidence: 99%
See 1 more Smart Citation